Knowledge management concepts, methodologies, tools, and applications - Jennex, Murray E., 1956- (Contemporary research in information science and technology., 2008)
"This is the defining reference source for all theories, concepts, and methodologies within the KM discipline. It includes chapters on Implementing KM in Organizations; KM Systems Acceptance; KM Communication; Knowledge Representation; Knowledge Sharing; KM Success Models; Knowledge Ontology; and Operational KM, and provides libraries with the defining reference to the field"--Provided by publisher.